2016
DOI: 10.1080/03019233.2016.1214379
|View full text |Cite
|
Sign up to set email alerts
|

An improved lance design for hot metal de-sulphurisation

Abstract: Hot metal de-sulphurisation is a dip-lance process involving the pneumatic injection of fine-grained de-sulphurisation reagents into the molten metal. For maximum efficiency the particles must be dispersed in the ladle as widely as possible to increase the total interfacial area which is primarily controlled by the lance design. Seven different lance configurations were modelled and simulated to determine the most efficient design using physical and mathematical modelling approach. A 0.25 scale plexi-glass mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 9 publications
2
20
0
Order By: Relevance
“…The flow fields calculated for reagent injection with a submerged lance in ladles are qualitatively similar to the results of the CFD simulations by Pirker et al for slag regeneration using an injection of oxygen with an eccentrically positioned submerged lance. Similar to El‐Kaddah and Szekely, Pirker et al reported that the bath movement was more vigorous using deeper position of the lance.…”
Section: Modeling Of Fluid Flow Phenomenasupporting
confidence: 81%
See 4 more Smart Citations
“…The flow fields calculated for reagent injection with a submerged lance in ladles are qualitatively similar to the results of the CFD simulations by Pirker et al for slag regeneration using an injection of oxygen with an eccentrically positioned submerged lance. Similar to El‐Kaddah and Szekely, Pirker et al reported that the bath movement was more vigorous using deeper position of the lance.…”
Section: Modeling Of Fluid Flow Phenomenasupporting
confidence: 81%
“…Recently, Tripathi et al used physical modeling and a multiphase CFD model to study the effect of seven different lance port designs on mixing time in the case of desulfurization with CaC 2 in a ladle. As for simulations for a real ladle, hot metal, gas, and particles were considered as continuous phase, dispersed gas phase, and dispersed solid phase, respectively.…”
Section: Modeling Of Fluid Flow Phenomenamentioning
confidence: 99%
See 3 more Smart Citations